Information system planning strategy on higher education institution based computer: a case study of a STIKOM yos sudarso purwokerto Indonesia - Wibowo, Adhi; Nugroho, Ariadi; Marbun, Padosroha; Chika Fransi, Diandra (International Journal of Engineering and Technology, 2018)
The study aims to describe planning strategies of information technology and information system on higher education based computer, especially College of Computer Science Yos Sudarso Purwokerto or â€œSekolah Tinggi Ilmu Komputer Yos Sudarso Purwokertoâ€ (STIKOM Yos Sudarso Purwokerto) Indonesia. The method was Enterprise Architecture Framework, in which each components of framework must utilities some analysis like SWOT analysis, IT Balanced Scorecard and Portfolio Application Framework. The result from Enterprise Architecture Framework documentation, can give a description to institution about development strategy of information system which is compatible with higher education institution vision and mission, as well as give input related to technology infrastructure condition and resource of institution. It is hoped that the blueprint can be implemented as a manual for developing institution.Â Â